2023
DOI: 10.3390/molecules28135199
|View full text |Cite
|
Sign up to set email alerts
|

A Waterborne Epoxy Composite Coating with Smart Corrosion Resistance Based on 2-Phenylbenzimidazole-5-sulfonic Acid/Layered Double Hydroxide Composite

Abstract: In this study, ZnAl-layered double hydroxide (ZnAl-LDH) was functionalized with 2-Phenylbenzimidazole-5-sulfonic acid (PBSA) to prepare ZnAl-PBSA-LDH using a simple one-step method. The electrochemical impedance spectroscopy (EIS) result of the solution phase demonstrated excellent corrosion inhibition performance of ZnAl-PBSA-LDH. Subsequently, 0.6 wt.% ZnAl-PBSA-LDH with shielding effects and active inhibition was incorporated into the water-based epoxy (WEP) for preparing the high-performance anti-corrosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…As depicted in Figure a, the WEC displayed a smooth cross section with several deep holes (red circle). These holes serve as pathways for corrosive media to permeate the WEC, which leads to the corrosion of protected metal . In Figure b, the cross section of MX/WEC appeared rougher with shallower holes compared with those of WEC (Figure b).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As depicted in Figure a, the WEC displayed a smooth cross section with several deep holes (red circle). These holes serve as pathways for corrosive media to permeate the WEC, which leads to the corrosion of protected metal . In Figure b, the cross section of MX/WEC appeared rougher with shallower holes compared with those of WEC (Figure b).…”
Section: Resultsmentioning
confidence: 98%
“…These holes serve as pathways for corrosive media to permeate the WEC, which leads to the corrosion of protected metal. 34 In Figure 5b, the cross section of MX/WEC appeared rougher with shallower holes compared with those of WEC (Figure 5b). However, the presence of uneven jagged cracks in MX/WEC suggested poor compatibility between MXene and WEC.…”
Section: Chemical and Physical Propertiesmentioning
confidence: 92%
“…Therefore, LDHs have great application prospects in conversion coatings or as nanofillers for polymer coatings. 125…”
Section: Applications Of 2d Transition Metal Layered Materials In Cor...mentioning
confidence: 99%
“…[4,5] However, micropores/microcracks easily emerge in WEP coating due to water evaporation during the curing process, allowing the penetration and diffusion of corrosive media within the coating and resulting in the degeneration of corrosion resistance. [6,7] It was reported that the incorporation of two-dimensional nanosheet fillers (such as BN, [7] GO, [8,9] LDH, [10] etc.) could effectively reduce/avoid micropores/microcracks of the filler/WEP composite coatings and enhance the corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%